Enhancing agricultural sustainability through micro-irrigation - Ashok Gulati; Ankana Rana; Ritika Juneja (University of Bonn, Center for Development Research (ZEF), 2025)
This paper delves into the significant impact of micro-irrigation systems on agricultural sustainability in India. By analysing the evolution of micro-irrigation, government schemes promoting its adoption, case studies on benefit-cost analysis, challenges faced, and success stories, this paper aims to provide a comprehensive understanding of how micro-irrigation can revolutionize the agricultural landscape in India. The study compares the impact of drip irrigation adoption on various factors such as electricity consumption, costs, benefits, water use efficiency, and overall productivity. Through a detailed examination of the benefits of micro-irrigation systems on different crops and regions in India, this paper highlights the crucial role of this technology in achieving sustainable agriculture.
Keywords: Q12; Q15; Q25; Q55; 330; irrigation; micro-irrigation; India; irrigation technology; cost-benefit analysis